Co-proxamol and suicide: a study of national mortality statistics and local non-fatal self poisonings. Issue 7397 (10th May 2003) - Hawton, Keith; Simkin, Sue; Deeks, Jonathan
Abstract: Objectives: To examine the incidence of suicides due to co-proxamol compared with tricyclic antidepressants and paracetamol, and to compare fatality rates for self poisonings with these drugs. Design: Analysis of routinely collected national and local data on suicides and self poisonings. Setting: Records of suicides in England and Wales 1997-9; non-fatal self poisonings in Oxford District 1997-9. Data sources: Office for National Statistics and Oxford monitoring system for attempted suicide. Main outcome measures: Incidence of suicides with co-proxamol or tricyclic antidepressants or paracetamol. Ratios of fatal to non-fatal self poisonings. Results: Co-proxamol alone accounted for 5% of all suicides. Of 4162 drug related suicides, 18% (766) involved co-proxamol alone, 22% (927) tricyclic antidepressants alone, and 9% (368) paracetamol alone. A higher proportion of suicides in the 10-24 year age group were due to co-proxamol than in the other age groups. The odds of dying after overdose with co-proxamol was 2.3 times (95% confidence interval 2.1 to 2.5) that for tricyclic antidepressants and 28.1 times (24.9 to 32.9) that for paracetamol. Conclusions: Self poisoning with co-proxamol is particularly dangerous and contributes substantially to drug related suicides. Restricting availability of co-proxamol could have an important role in suicide prevention.